Rational Choice Institutionalism of Reclamation Permits at the Department of Marine and Fisheries Kepulauan Riau Province - Fitri Kurnianingsih; Oksep Adhayanto; Mahadiansar Mahadiansar; Ramadhani Setiawan (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2022)
This study will analyze the modification of reclamation permits in the Riau Islands Province (Kepri) to overcome various reclamation difficulties that are local and national challenges. Based on Governor's Regulation Number 26 of 2017 concerning Procedures for Granting Reclamation Permits in Coastal Areas and Small Islands, reclamation permits are in the hands of the Governor. However, in 2018, Pergub Number 31 of 2018 concerning the Implementation of One-Stop Services for the Riau Islands Province in Article 8 states that the Governor delegates licensing and non-licensing authority which are the affairs of the Riau Islands Provincial Government to regional heads of the relevant services. Rational Choice Institutionalism will evaluate the interaction process of relevant agencies and other players in the reclamation permit procedure within the boundaries of institutions that control and limit the activities of policy actors. The study technique used is qualitative with an interpretive analysis of each actor to describe the motivation to employ institutions as a reasonable choice. The results show that the process that occurs in the reclamation permit in the Riau Islands Province is the rational choice of institutionalism, namely the link between actors and the surrounding institutions. The need for changes to the performance and behavior of good institutionalism towards cooperation between other stakeholder actors for changes to good reclamation permits on an ongoing basis by the Kepri Provincial Government.